Effects of Price, Promotion, and Product Quality on Customer Satisfaction of Oppo Smartphone - Effy Zalfiana Rusfian; Evalina Evalina; Iskandar Ahmaddien (Jurnal Mantik, 2022)
More emerging smartphone vendors offers a variety of smartphones with existing qualities. Oppo smartphone which is made in China is popular in Indonesia and has high demand in Indonesia. This study aims to identify how price, promotion, and product quality affect customer satisfaction of Oppo smartphone products. The study involved 44 participants. The data were collected using a questionnaire. The data were analyzed using multiple linear regression analysis with the help of IBM SPSS version 26 and data management applications.